Smart and sustainable planning for cities and regions. Results of SSPCR 2017. - (:unkn) unknown (Springer, 2018)
The book comprises a selection of the top contributions presented at the second international conference "Smart and Sustainable Planning for Cities and Regions 2017 (SSPCR) ", held in March 2017 in Bolzano, Italy. Featuring forty-six papers by policy-makers, academics and consultants, it discusses current groundbreaking research in smart and sustainable planning, including the progress made in overcoming cities' challenges towards improving the quality of life. Climate change adaptation and mitigation of global warming, generally identified as drivers of global policies, are just the "tip of the iceberg" when it comes to smart energy transition. Indeed, equally relevant towards this current transformation - and key topics in this volume - are ICTs, public spaces and society; next economy for the city; strategies and actions for good governance; urban-rural innovation; rethinking mobility. The book's depth in understanding and insightfulness in re-thinking demonstrate the breaking of new ground in smart and sustainable planning. A new ground that policy-makers, academics and consultants may build upon as a bedrock for smart and sustainable planning.
Keywords: Stadtplanung; Stadtentwicklungsplanung; Regionalplanung; Informationstechnologie; Kommunikationstechnologie; Stadtökologie; Planungstheorie; Planungspraxis; Smart City; Nachhaltige Entwicklung